The Restorative Justice Based Health Criminal Law Policy: Orientation and Formulation - Darma, I Made Wirya; Arifin, Zainal; ary Mahadnyani, Tjokorda Mirah (Faculty of Law, Universitas Pekalongan, 2024)
Health criminal law policies are important in maintaining community welfare. Complex issues involve law enforcement against illegal drugs, alcohol, smoking, and mental health problems, with ethical considerations regarding the use of punishment versus rehabilitation. The aim of this research is to analyze the integration of a restorative justice orientation in health criminal law policy and evaluate its impact on the effectiveness of law enforcement in protecting public health, as well as identifying obstacles and challenges in its implementation in Indonesia. This research uses a document analysis approach to examine legislation related to health criminal law and the concept of restorative justice, as well as a qualitative approach in data analysis to formulate health criminal law policies based on restorative justice from various legal documents and relevant literature. The research results show that the Restorative Justice Orientation can be integrated into health criminal law policies with various positive impacts, including recovery in dealing with public health violations, rehabilitation without unnecessary criminalization, community involvement, victim recovery, community safety, public education, and cross-border cooperation. sector. Evaluation and revision of policies is important to create a fairer and more sustainable legal system. However, the implementation of this policy in Indonesia has complex challenges such as low public awareness of the concept of restorative justice, limited resources, unequal access to health services, changes in legal culture, injustice, and the role of legal institutions that must be changed